Gastrocnemius Musculocutaneous Chimeric Flap- A Study On The Use Of Differential Movement Of Muscle And Skin - Yadav, Srinivas; M, Kumaraswamy; R, Aravind; Pasar, Santoshi (Journal of Neonatal Surgery, 2025)
Background: Gastrocnemius muscle flap is commonly used flap for reconstruction of defects around the knee. Defects bigger than the width of the flap would require a second flap or a free flap. We have tried to use the gastrocnemius musculocutaneous flap using differential movement of the muscle and skin to improve the area of the defect that can be covered. Aim: To study the differential movements of skin and muscle of the gastrocnemius musculocutaneous flap. Methodology: It was a retrospective case record analysis at a tertiary care hospital conducted between Jan 2016 to Dec 2019. We had 5 cases who underwent the gastrocnemius musculocutaneous flap with differential movement of the muscle and the skin. We used the skin which was laterally advanced, propelled at varying angles to cover the defect. Results: We had 5 cases with the flap. All the flaps survived. We had propeller flaps in 4 cases and lateral advancement in 1 case. All our flaps survived. Conclusion: Gastrocnemius Musculocutaneous flap can be better utilized with a chimeric principle and using the differential movement. This allows better movement and increases in surface area of the flap. The flap is easy to harvest, ability to cover large surface area, no dog ears as in Musculo-cutaneous flaps, movement of the fascio-cutaneous flap by advancement, or propel the flap if a single perforator can reliably support the vascularity.